2020
DOI: 10.1186/s12944-020-01383-8
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes of lipid profile in severe hypertriglyceridemia-induced acute pancreatitis patients under double filtration plasmapheresis: a retrospective observational study

Abstract: Background To investigate the dynamic change of lipid profile under double filtration plasmapheresis (DFPP) in severe hypertriglyceridemia-induced acute pancreatitis (sHTGP) patients and ascertain the association between these changes and the clinical prognosis. Methods sHTGP patients admitted within 72 h after disease onset were included, and all the patients received DFPP within 24 h after admission. Lipid profile were detected on admission, consecutive 4 days after DFPP and at discharge. Results There w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
(46 reference statements)
2
4
0
Order By: Relevance
“…This may be related to a higher incidence of metabolic syndrome [29] and, in particular, alcohol-related HTG in the male gender [30,31]. Moreover, they demonstrated that triglycerides were effectively reduced by plasma exchange [14], as did several other studies [10,[32][33][34]. These findings are comparable to the results of our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This may be related to a higher incidence of metabolic syndrome [29] and, in particular, alcohol-related HTG in the male gender [30,31]. Moreover, they demonstrated that triglycerides were effectively reduced by plasma exchange [14], as did several other studies [10,[32][33][34]. These findings are comparable to the results of our study.…”
Section: Discussionsupporting
confidence: 91%
“…In patients with severe hyperlipidemia refractory to diet and lipid-lowering drugs, apheresis is the therapy of choice. There is a large body of literature that demonstrates that apheresis is a very effective and safe treatment for lowering cholesterol levels [32,33,[39][40][41]. In this context, Chen et al [42] showed that plasmapheresis was more effective in terms of lowering triglycerides for patients with HTGP and high cholesterol levels (>12.4 mmol/L) compared to low cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
“…To compensate for the slow effect of pharmacological therapies, DFPP was performed in sHTGP patients and has been proven effective for decades 6,10 . The efficacy of DFPP was tested in 47 sHTGP patients by Zheng et al, who discovered that the parameters were altered dramatically on the first day after DFPP 11 . This study revealed similar results, and the effect was maintained until discharge.…”
Section: Discussionmentioning
confidence: 91%
“…Double ltration plasmapheresis (DFPP) is a selective method of TPE [20] . Because DFPP has the advantage of reducing the need for fresh frozen plasma (FFP) as a replacement uid and signi cantly reducing the risk of allergic reactions and viral infections secondary to FFP, it has been increasingly used to treat HTG-AP in recent years [20][21][22][23][24][25][26][27] . However, there is little evidence to conclude that DFPP has an effect on improving outcomes of patients with HTG-AP, particularly in terms of reducing organ injury [22][23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…However, there is little evidence to conclude that DFPP has an effect on improving outcomes of patients with HTG-AP, particularly in terms of reducing organ injury [22][23][24][25] . It has been reported that rapid TG clearance by DFPP in the clinical setting may not translate into a theoretical effect [26][27] . As mentioned in the relevant literature, the timing of apheresis treatment may be critical to its effect on the outcomes in the early stage of HTG-AP [4,15,28−29] .…”
Section: Introductionmentioning
confidence: 99%